Benchmarking of secondary schools based on students’ results in higher education - Silva, Maria C. A. (2022)
The performance of secondary schools is usually assessed based on students’ results on national exams at the end of secondary education. This research uses data on academic achievements by first-year univer- sity students to benchmark secondary schools on their ability to lead students to success in higher edu- cation. The analysis is conducted using data of University of Porto and Catholic University of Porto, Portu- gal, for a three-year period, corresponding to more than 10.0 0 0 students from 65 degrees, for which the school of origin is known. A number of variables representing students’ success in Higher education were constructed for each school in our sample and aggregated through a Benefit of the Doubt indicator. Re- sults suggest that the schools’ ranking based on schools’ ability to prepare students for university success is quite different from the ranking based on results on national exams. Given these findings, we propose complementing schools’ performance assessments (traditionally based on national exam results or indi- cators of value added) with indicators that account for the preparation of students for success in future challenges, which is indisputably a key objective of secondary education. We propose a composite indi- cator for the analysis of these complementary aims as well, and results show that frontier units indeed exhibit trade offs between traditional measures of performance and our new measure of performance.